2020
DOI: 10.1177/1090198120914249
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy in Researching and Obtaining Medical Cannabis by Patients With Chronic Conditions

Abstract: Background. Due to the increasing availability of medical-grade cannabis for treatment of chronic conditions, we examined how prospective users navigate the process of researching, procuring, and using cannabis. Given the barriers prospective users experience, self-efficacy may be a factor for those who incorporate cannabis into treatment. Aims. The purpose of this study was to identify behaviors associated with self-efficacy in the context of researching, procuring, and using cannabis. We analyzed narratives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In this context, he observed that those patients with higher self-efficacy about medical cannabis were more likely to engage in activities to experiment and incorporate medical cannabis into their medical management despite the perspective of their providers about this treatment modality. 38 These findings may provide a take into our results that 89% of the assessed medical cannabis patients considered that cannabis is better than opioids for their pain management.…”
Section: Discussionmentioning
confidence: 70%
“…In this context, he observed that those patients with higher self-efficacy about medical cannabis were more likely to engage in activities to experiment and incorporate medical cannabis into their medical management despite the perspective of their providers about this treatment modality. 38 These findings may provide a take into our results that 89% of the assessed medical cannabis patients considered that cannabis is better than opioids for their pain management.…”
Section: Discussionmentioning
confidence: 70%
“…Typical use of PDCs for therapeutic intent involves the patient trialing multiple different products and varieties of cannabis indiscriminately. 37 PDCs for medical use may be purchased from unlicensed sellers or obtained from unknown sources through friends and family. 32 We challenge MC service providers to demand that LPs provide a high-quality, reliable product with pharmacokinetic testing and stability data.…”
Section: Discussionmentioning
confidence: 99%
“…36 Studies reveal that patients rely on experimentation with different dosage forms and plant cultivars, seek advice from retail associates or friends, or research online to fuel self-efficacy for the use of MC. 37 Further unearthing this issue, several observational studies suggest that patients do not fully understand the risks of cannabis use. 24,38 An alarming 76% of Canadian MC users reported that they expected no problems when combining cannabis with other medications.…”
Section: Description and Disposition Of Patients With Cancer Accessin...mentioning
confidence: 99%
“…Moreover, involving patients in the construction of such studies should also add relevant elements to the analysis. Indeed, directly involving patients in research, in the recruitment or tools development, could help better assess these challenges and facilitators in patients’ self-management [ 20 , 21 ], since they can help identify crucial elements that could have otherwise been overlooked. [ 22 – 24 ].…”
Section: Introductionmentioning
confidence: 99%